Theodor Heuss, In der Defensive - Heuss, Theodor (Briefe, 2009)
Under the National Socialist regime, Theodor Heuss was rapidly forced onto the defensive. He lost nearly all his public offices and posts, yet as a publicist Heuss continued to defend his liberal convictions. We encounter a member of the educated middle classes who attempted to carve out space for himself in a hostile political environment. These 194 selected letters, most of them previously unknown, reflect his gripping biography and the dramatic course of events from the handing over of power to the National Socialists in January 1933 to the end of the war in 1945.